International investments and venture capital in the context of growing economic security: challenges for trade organization in EU countries - Novik, Iryna; Suslikov, Stanislav; Matrosova, Victoria; Honchar, Iryna (Національний технічний університет "Харківський політехнічний інститут", 2024)
This document extensively examines the challenges faced by EU countries in organizing trade amidst the presence of international investments and venture capital within the context of increasing economic security. The article discusses the impact of venture capital and international investments on the development of the country, analyzing their influence on economic security in EU countries. As a result of investments, on one hand, the country gains more opportunities for positive development across various sectors and promotes active engagement in implementing new ideas into the realm of trade. On the other hand, new tasks arise for the country regarding the regulation and organization of trade, as well as control over capital and the overall state of the economy. Additionally, the article explores strategies that can be utilized to ensure effective trade organization amidst growing economic stability. The pace of modern trade development always demands proactive measures to improve trade processes. Therefore, countries need to continuously evolve, implement new ideas, and ensure the economic security of the nation to remain competitive and foster trade growth. The state of investment and innovation security of Ukraine was considered. The main challenges and threats in the field of investment and innovation security were identified. As a result of the systematization of the main provisions related to international investments and venture capital in the conditions of growing economic security, the main tasks in the field of ensuring the economic security of the state and for the organization of trade in the EU countries were proposed.

У цій статті детально досліджуються виклики, що постають перед країнам ЄС для організації торгівлі за наявності міжнародних інвестицій та венчурного капіталу в умовах зростаючої економічної безпеки. Стаття обговорює питання впливу венчурного капіталу та міжнародних інвестицій на розвиток раїни, аналізує їх вплив на економічну безпеку в країнах ЄС. За рахунок інвестицій перед країною з одного боку з’являється більше можливостей щодо позитивного розвитку у багатьох сферах, та сприяє активній діяльності щодо впровадження нових ідеї в сферу торгівлі. З іншого боку перед країною виникають нові завдання щодо регулювання та організації торгівлі та контролю над капіталом та загальних станом економіки. Також стаття розглядає стратегії, які можуть бути використані для забезпечення ефективної організації торгівлі в умовах зростаючої економічної стабільності. Темпи сучасного розвитку торгівлі завжди потребують активних дій щодо удосконалення процесів торгівлі, тому країнам необхідно постійно розвиватися, впроваджувати нові ідеї та забезпечувати економічну безпеку країни для того, щоб залишатися конкурентоспроможним та розвивати торгівлю. Розглянуто стан інвестиційно-інноваційної безпеки України. Було виявлено основні виклики та загрози у сфері інвестиційно-інноваційної безпеки. У результаті систематизації основних положень повязаних з міжнародними інвестиціями та венчурним капіталом в умовах зростаючою економічної безпеки були запропоновані основні завдання у сфері забезпечення економічної безпеки держави та для організації торгівлі в країнах ЄС.
Міжнародні інвестиції та венчурний капітал в умовах зростаючої економічної безпеки: виклики для організації торгівлі в країнах ЄС
Keywords: economic security; international investment; venture capital; innovative projects; competitiveness; product quality; development strategies; економічна безпека; міжнародні інвестиції; венчурний капітал; інноваційні проекти; конкурентоспроможність; якість продукції; стратегії розвитку